Experimental trials on the use of radioimmunoassay for the detection of leptospiral antigens in urine - Bahaman, Abdul Rani; Marshall, R. B.; Moriarty, K. M. (Elsevier, 1986)
Trials were conducted on the use of the solid phase radioimmunoassay (RIA) to detect leptospires or their antigens in simulated urine samples. The procedure was relatively simple to perform and appeared to be specific in detecting certain numbers of leptospiral organisms or their antigens in experimentally prepared samples. With this technique, it was possible to examine individual or pooled urine samples for the presence of leptospires within half a day. This technique may be of value for the detection of leptospiruric animals if the sensitivity of the technique could be further increased. Suggestions for the improvement of the procedure are discussed